Osteosynthesis of periprosthetic type A and B femoral fractures using an unlocked plate with integrated cerclage cable and trochanteric hook: A multicenter retrospective study of 45 patients with mean follow-up of 20 months. Issue 12 (December 2017) - Gavanier, B.; Houfani, F.; Dumoulin, Q.; Bernard, E.; Mangin, M.; Mainard, D.
Abstract: Introduction: Femoral periprosthetic fracture (FPF) is a frequent complication in dependent elderly persons, with a limited life expectancy. Their management is difficult and the choice between osteosynthesis and prosthesis is still matter of discussion. To date, there is no study on unlocked plate with integrated cerclage cable and trochanteric hook for this indication. The objectives of this study were to analyze fracture healing, complication rate and functional outcome. Our hypothesis is that this technique allows a high rate of consolidation and a return to the previous state in terms of autonomy and place of residence. Materials and methods: We conducted a retrospective multicenter study between 2010 and 2015. The inclusion criteria were: patients with type A and B FPF according to the classification of Vancouver who received osteosynthesis hook plate. The evaluation focused on the consolidation period, complications and pre and postoperative Parker and Katz scores. Death, nonunion, dislocation, infection and failure of fixation were considered major complications. Results: Forty-five patients met the inclusion criteria and were evaluated at mean 20 months (6–72). All fractures consolidated at a mean 7 weeks (6–10), except one that has not undergone further surgery in the absence of functional impairment. Parker score decreased from 6.4 to 4.9 (p = 0.03) and Katz score from 4.8 to 4.3 (p = 0.045). Five patients died within the year of the operation. Five patients living at home preoperatively were admitted to an institution, the others returned to their retirement home or nursing home. Conclusion: This plate allows for a quick and effective management of patients with FPF. The low rate of complications and the very good consolidation rate lead us to use the same plate even for class B2 or B3 fractures in some patients with precarious health condition who cannot tolerate major revision surgery: Elderly, ASA score >3, loss of autonomy, Katz score <4.